Risk factors and outcomes of lower respiratory tract infections after traumatic brain injury: a retrospective observational study - Caceres, Eder; Olivella, Juan C.; Yanez, Miguel; Viñan, Emilio; Estupiñan, Laura; Boada, Natalia; Martin-Loeches, Ignacio; Reyes, Luis Felipe (Frontiers in Medicine, 2023)
Background: Traumatic Brain Injury (TBI) is a public health problem with a high burden in terms of disability and death. Infections are a common complication being respiratory the most frequent source. Methods: This observational, retrospective, single-center cohort study describes the clinical features and factors associated with Lower Respiratory Tract Infections (LTRI) in patients with TBI admitted to Intensive Care (ICU). We used univariate and multivariable analysis to identify the risk factors associated with developing LRTI. Results: We included 291 patients of whom 77% (225/291) were male. The median (IQR) age was 38 (28-52). The most common cause of injury was road traffic accidents, 72% (210/291), followed by falls 18% (52/291), and assault at 3% (9/291). The median (IQR) Glasgow Coma Scale (GCS) on admission was 9 (6-14), and 47% (136/291) were classified as severe TBI, 13% (37/291) as moderate, and 40% (114/291) as mild. The median (IQR) ISS (Injury Severity Score[ELCR1]) [ELCR2]was 24 (16-30). 48% (141/291) of patients presented at least one infection during hospitalization, and from those, 77% (109/141) were classified as LTRI, which includes tracheitis 55% (61/109), ventilator-associated pneumonia (VAP) 34% (37/109) and hospital-acquired pneumoniae (HAP) 19% (21/109). After the multivariable analysis, the following variables were significantly associated with LTRI: age (OR 1.1, 95%CI 1.01-1.2), severe TBI (OR 2.7 95%CI 1.1-6.9), AIS thorax (OR 1.4 95 CI 1.1-1.8) and mechanical ventilation on admission (OR 3.7 95%CI 1.1-13.5). At the same time, hospital mortality did not differ between groups (LTRI 18.6% versus No LTRI 20.1%, p=0.7), ICU and hospital LOS (Length of stay) were longer in the LTRI group (median [IQR] 12 [9-17] versus 5 [3-9], p<0.01) and (median [IQR] 21 [13-33] vs. 10 [5-18], p=0.01), respectively. Time on the ventilator was longer for those with LTRI. Conclusion: The most common source of infection in patients with TBI admitted to ICU is respiratory. Age, severe TBI, thoracic trauma, and mechanical ventilation were identified as potential risk factors. LTRI was associated with prolonged ICU, hospital stay, and more days on the ventilator but not with mortality.